Sexual Violence against Women in Marital Dyads, Prevalence, Correlates, and Consequences: Among the Ijesa of South-Western Nigeria - Ajala, Adebayo Olukunle (Archives of Business Research, 2017)
Sexual violence is of a global public health concern. However, population-based studies of its determinants and reproductive health consequences remain scarce in Nigeria. The paper therefore sets to fill this gap. The results showed that 42.7% of all female respondents experienced sexual violence. The logistic regression results showed that religion, occupation, type of marital union, desire for another child, age at marriage, knowledge of husband’s extra-marital relationship, the husband’s education, occupation, spousal age difference, sleeping together with husband on same bed, and couples sharing secrets are factors that significantly affect the chances of experiencing violence. Women who have experienced sexual violence significantly have more births and had higher prevalence of STIs than those who never experienced sexual violence. Endurance is the main coping strategy employed by women who have experienced sexual violence. In sum, sexual violence has negative reproductive health consequences on women. The results underscore the need to prevent its incidence.